Legal Protectıon Of The Economıc Rıghts Of Tengger People Regardıng The Partnershıp Pattern Wıth Bromo Tengger Semeru Natıonal Park Offıce - Shrimanti Indira Pratiwi; I Nyoman Nurjaya; Imam Koeswahyono; Djumikasih Djumikasih (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Tengger people are allowed to carry out activities in the Bromo Tengger Semeru national park area through a conservation partnership mechanism that includes traditional zones and religious, cultural and historical zones. Based on regional zoning data owned by the Bromo Tengger Semeru national park office, the total area of the both zones where the conservation partnership is carried out is only ± 84 hectares, while the Tengger people’s main livelihood is a farmers and that policy has a big impact on the economic rights of the Tengger people. One of the unresolved problems is how to change the government’s paradigm which is only oriented towards economic growth for development to a paradigm which prioritizes the economic rights of traditional communities around the national park. This research is normative legal research with a statutory, conceptual and analytical approach. The conclusion of this research is that the conservation partnership is not enough to guarantee the economic rights of the Tengger people because the pattern is based on ecological sensitivity method andi is carried out unilaterally by the national park office. There is a need genuine public participation from Tengger people, starting from the formulation of policy regulations to the evaluation level so that the economic rights of the Tengger people can be guaranteed.